2013
DOI: 10.4335/12.1.55-78(2014)
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Transparency in Sustainability Reporting by Local and Regional Governments

Abstract: Although the importance of sustainability reporting in the public sector is widely recognized, there are few studies about this issue. This paper analyzed the practices of diffusion of information on sustainability in local governments. So, we observed the Websites of the largest local governments in Spain using a list of items from the guidelines of GRI and comparing the results with the results of the Spanish regional governments. Our findings show that local governments reported some information (50% of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 0 publications
1
32
0
Order By: Relevance
“…Some previous studies have analysed the disclosure of general or financial information on LG websites [16,53]. In recent years, studies of sustainability transparency in public administration and public utilities have also appeared [17][18][19][54][55][56][57] and several papers have analysed the disclosure of sustainability information by LGs. For example, one study [17] described an exploratory analysis of six European cities, while another [58] focused on the annual sustainability reports of four LGs in Australia.…”
Section: Sustainability Transparency and Administrative Culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some previous studies have analysed the disclosure of general or financial information on LG websites [16,53]. In recent years, studies of sustainability transparency in public administration and public utilities have also appeared [17][18][19][54][55][56][57] and several papers have analysed the disclosure of sustainability information by LGs. For example, one study [17] described an exploratory analysis of six European cities, while another [58] focused on the annual sustainability reports of four LGs in Australia.…”
Section: Sustainability Transparency and Administrative Culturesmentioning
confidence: 99%
“…In recent years, many papers have been published on the question of online transparency by LGs [14][15][16], and some have considered the question of online disclosure of sustainability information [12,13,[17][18][19], but in most cases only a partial analysis of the situation is presented. In addition, although research findings suggest that cultural differences can affect accountability and transparency [20][21][22], few studies have been undertaken to address the question of transparency on sustainability from the perspective of the cultural traditions prevailing in different countries [23,24], or to analyse factors that may influence this information disclosure.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the governmental disclosure of sustainability-related information has attracted considerable research interest. Thus, many papers have recently been presented on information disclosure by the public sector, and especially by local and regional governments in Europe [6,19,25,28,36,[43][44][45][46].…”
Section: Prior Research On Local Government Transparency On Sustainabmentioning
confidence: 99%
“…Due to their size and inuence, public agencies are expected to take the lead by publicizing their activities in order to promote sustainability. However, their sustainability reports are proceeding more slowly than those of other sectors (Greiling & Grüb, 2014, Domingues, Lozano, Ceulemans & Ramos, 2017, and there is little research related to social and environmental accounting, accountability, and sustainability in the public sector and the third sector (Adams, Muir & Hoque, 2014;Alcaraz-Quiles, Navarro-Galera & Ortiz-Rodríguez, 2014;Domingues, Lozano, Ceulemans & Ramos, 2017;Dumay et al, 2010;Greiling et al, 2015), even though numerous authors have reported on its importance (Alcaraz-Quiles et al, 2014;Ball & Bebbington, 2008;Ball, Grubnic & Birchall, 2014;Ball & Osborne, 2011;Greiling et al, 2015;Gray et al, 2014). Additionally, many of the studies in this area are related exclusively to a single country or to a specic type of organization (Papenfuß, Grüb & Frieländer, 2015).…”
Section: Introductionmentioning
confidence: 99%